2007
DOI: 10.1111/j.1365-2133.2007.08235.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphoea: a manifestation of infection with Borrelia species?

Abstract: FFM is a reliable and highly sensitive method to detect Borrelia in tissue sections. The frequent detection of this microorganism in morphoea points to a specific involvement of B. burgdorferi or other similar strains in the development of or as a trigger of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 58 publications
1
46
1
4
Order By: Relevance
“…Second, the involvement was severe leading to significant gingival recession, bone resorption and external tooth resorption. Third, no potential triggering factor, such as trauma, radiation or B. burgdorferi infection [29] was identified. Multiple drugs have been implicated in the development of morphea-like lesions [30].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the involvement was severe leading to significant gingival recession, bone resorption and external tooth resorption. Third, no potential triggering factor, such as trauma, radiation or B. burgdorferi infection [29] was identified. Multiple drugs have been implicated in the development of morphea-like lesions [30].…”
Section: Discussionmentioning
confidence: 99%
“…Infections such as those with Epstein-Barr virus, varicella, morbilli, or borreliosis, have been reported as underlying factors for the onset of morphea and furthermore they have been recommended as a possible trigger factors for morphea. Borrelia burgdorferi today is a possible etiologic factor [6]. Antibodies to B. burgdorferi and high antinuclear antibody titers have been described in patients with morphea, and it has been suggested that Borrelia-associated early-onset morphea may represent a subset of patients with infection-induced autoimmunity.…”
Section: Resultsmentioning
confidence: 99%
“…The studies with negative PCR results were more rigorous in that they investigated larger numbers of patients and applied more than one primer set. In other reports the association has been alleged based on diagnostic methods that are far less specific such as immunohistology, focus-floating microscopy, silver staining, or lymphoproliferative response assays (Buechner et al, 1995;Eisendle et al, 2007). In case reports, B. burgdorferi infection has been implicated in the causation of two additional sclerosing disorders, progressive facial hemiatrophy and eosinophilic fasciitis (Shulman syndrome), based on silver staining, immunohistology, or PCR (Stern et al, 1992;Granter et al, 1994).…”
Section: Borrelia Burgdorferi and Sclerosing Skin Conditionsmentioning
confidence: 99%